Studies on Solute-Solvent Interactions between Substituted Isoxazolines and Different Percentages of Dioxane-Water and Methanol-Water Mixture - Patil, M.P.; Narwade, M.L. (Asian Journal of Chemistry, 2010)
The present study deals with the study of molecular interactions in terms of viscosity β- coefficient of ligands such as 3-(5-chloro-2-hydroxyphenyl)-5-phenyl-Δ2-isoxazoline (L1), 3- (3-bromo-5-chloro-2-hydroxyphenyl)-5-phenyl-Δ2-isoxazoline (L2) and 3-(5-chloro-2- hydroxy-3-nitrophenyl)-5-phenyl-Δ2-isoxazoline (L3) in 70, 75, 80, 85% percentage of dioxane-water and methanol-water mixtures.